Nitrogen-Bridged, Natural Product-Like Octahydrobenzofurans and Octahydroindoles: Scope and Mechanism of Bridge-Forming Reductive Amination via Caged Heteroadamantanes - Wales, Steven M.; Adcock, Holly V.; Lewis, William; Hamza, Daniel; Moody, Christopher J. (Wiley-VCH Verlag, 2018)
The biological significance of sp3-rich synthetic scaffolds with natural product-like features yet distinct global frameworks is being increasingly recognised in medicinal chemistry and biochemistry. Taking inspiration from the vast array of bioactive, bridged alkaloids, we report the synthesis of unique, densely functionalised tricyclic scaffolds based on nitrogen-bridged, octahydrobenzofurans and octahydroindoles. These heterocycle-rich frameworks were assembled by a one-pot, two-step bridge-forming reductive amination process, which was shown to proceed via caged, heteroadamantane intermediates that thermodynamically drive an exo–endo epimerisation, enabling intramolecular azaMichael addition over the concave face of the fused bicyclic precursors. In addition to evaluating the scope of this aza bridge-forming reaction, further stereochemical complexity was introduced by subsequent diastereoselective ketone reductions and other manipulations. Finally, strategic diversity points (amino, carboxy) were decorated with common medicinal chemistry fragments, providing a set of exemplar derivatives with Lipinski compliant physicochemical properties.